2022
DOI: 10.3389/fphar.2022.755009
|View full text |Cite
|
Sign up to set email alerts
|

Non-Vitamin K Oral Anticoagulant After Transcatheter Aortic Valve Replacement: A Systematic Review and Meta-Analysis

Abstract: Objective: We aimed to compare non-vitamin K oral anticoagulants (NOACs) with a traditional antithrombotic such as vitamin K antagonist (VKA) and antiplatelet agents in patients after transcatheter aortic valve replacement (TAVR).Methods: We conducted a search in PubMed, EMBASE, and the Cochrane Library until November 2021 for studies involving comparisons of any type of NOACs, including dabigatran, apixaban, rivaroxaban, and edoxaban, with VKA or antiplatelet agents after TAVR. A comparison of NOACs versus VK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 54 publications
(73 reference statements)
2
6
0
Order By: Relevance
“…These results confirm those of other recently published meta‐analysis on the same field, 2,3 which include the newly available ATLANTIS trial (presented at the American College of Cardiology Congress 2021) and ENVISAGE‐TAVI AF trial, 4 and focus on patients with an indication for OAC. There are several limitations acknowledged by the authors, among them the absence of a patient‐level data, heterogeneity of the populations, and definition of the outcomes (i.e., the definition of major bleeding was accepted as reported by individual studies and the rate of gastrointestinal bleeding is unknown).…”
supporting
confidence: 88%
“…These results confirm those of other recently published meta‐analysis on the same field, 2,3 which include the newly available ATLANTIS trial (presented at the American College of Cardiology Congress 2021) and ENVISAGE‐TAVI AF trial, 4 and focus on patients with an indication for OAC. There are several limitations acknowledged by the authors, among them the absence of a patient‐level data, heterogeneity of the populations, and definition of the outcomes (i.e., the definition of major bleeding was accepted as reported by individual studies and the rate of gastrointestinal bleeding is unknown).…”
supporting
confidence: 88%
“…Previous meta-analyses for comparing DOACs versus VKA after TAVR included randomized controlled and observational studies and enrolled patients with concomitant indication for oral anticoagulation, and thus, not all enrolled studies comprised only patients with AF. 1921 These meta-analyses for comparing DOACs versus VKA after TAVR showed different mortality and thromboembolic outcomes. 1921…”
Section: Discussionmentioning
confidence: 99%
“…1921 These meta-analyses for comparing DOACs versus VKA after TAVR showed different mortality and thromboembolic outcomes. 1921…”
Section: Discussionmentioning
confidence: 99%
“…Anticoagulant therapy in patients with bioprosthetic valves who require long‐term anticoagulation is a subject of debate due to limited data on drug selection. Recently, studies on TAVI patients have shown that DOACs have similar efficacy and safety profiles to warfarin 13,14 . Furthermore, there is growing evidence that DOACs not only provide a safe and effective option but also offer net clinical benefits in patients with a history of surgical valve repair 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies on TAVI patients have shown that DOACs have similar efficacy and safety profiles to warfarin. 13,14 Furthermore, there is growing evidence that DOACs not only pro-vide a safe and effective option but also offer net clinical benefits in patients with a history of surgical valve repair. 15,16 However, there is…”
Section: Case Presentationmentioning
confidence: 99%